Kapabilitas Proses Pelatihan Analisis Statistika Pada PTK KKG Gugus 04 Arjasa - Rusdiana, Riza Yuli; Sari, Vega Kartika (Faculty of Mathematics and Natural Sciences - Universitas Lampung, 2025)
Classroom Action Research is conducted to improve teacher competency and professionalism in classroom learning activities. The results of classroom action research are presented in the form of a research report which among the processes requires data analysis, interpretation, and drawing conclusions. This community service activity was carried out in 2 stages, namely socialization and training, and continued with assignments. The target of the activity is the KKG Gugus 04 Arjasa. The training includes graphical presentation of data, frequency tables, comparison of the averages of two populations independently (independent t-test) and comparison of the averages of two populations in pairs (dependent t-test) using the Ms.Excel program. Based on the results of the evaluation of the assignment, it shows that the implementation of the training has met the specification standards set by the team and is capable based on the Cp index and statistically controlled process using I-MR.